1974
DOI: 10.3758/bf03198569
|View full text |Cite
|
Sign up to set email alerts
|

Retinal location and string position as important variables in visual information processing

Abstract: Three experiments were conducted to isolate the effects of retinal locus and string position in tachistoscopic letter recognition. Retinal locus proved to be an important variable even when its range' was restricted to less than a degree from the center of the fovea. Performance was maximal at the center of the fovea, dropping off rapidly to about 1.5 deg from the center. From that distance on, the decline in performance was quite gradual. String position was also an important factor. Retinal locus and string … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 9 publications
2
40
0
1
Order By: Relevance
“…The presence of a stimulus item with similar features to the target item on either side of the target item can act as a lateral mask to affect stimulus identification (Hollingsworth & Wolford, cited in Wolford, 1975;Wolford, 1975) and has demonstrated some hemispheric effects (Bouma, 1974;Bradshaw, Bradley, Gates, & Patterson, 1977). The retinal locus of the stimulus image has also been shown to affect identification of verbal stimuli (Estes & Wolford, 1971;Hershenson, 1969; White, 1970;Wolford & Hollingsworth, 1974) and has demonstrated some hemispheric differences (Hirata & Bryden, 1976;Lefton & Haber, 1974;McKeever & Gill, 1972a;Scheerer, 1974;White, 1973b;Wolford & Hollingsworth, 1974). Therefore, to help clarify the influence of lateral masking and retinal locus effects on hemispheric differences and to extend these findings to nonverbal stimulus items, these variables were included in the present study.…”
mentioning
confidence: 99%
“…The presence of a stimulus item with similar features to the target item on either side of the target item can act as a lateral mask to affect stimulus identification (Hollingsworth & Wolford, cited in Wolford, 1975;Wolford, 1975) and has demonstrated some hemispheric effects (Bouma, 1974;Bradshaw, Bradley, Gates, & Patterson, 1977). The retinal locus of the stimulus image has also been shown to affect identification of verbal stimuli (Estes & Wolford, 1971;Hershenson, 1969; White, 1970;Wolford & Hollingsworth, 1974) and has demonstrated some hemispheric differences (Hirata & Bryden, 1976;Lefton & Haber, 1974;McKeever & Gill, 1972a;Scheerer, 1974;White, 1973b;Wolford & Hollingsworth, 1974). Therefore, to help clarify the influence of lateral masking and retinal locus effects on hemispheric differences and to extend these findings to nonverbal stimulus items, these variables were included in the present study.…”
mentioning
confidence: 99%
“…Estes, Allmeyer, and Reder (1976) found that positional uncertainty exists in linear displays, and Strangert and Brannstrom (1975) and Wolford and Hollingsworth (1974)have shown that spatial proximity of target and noise impairs target recognition and decision time. If positional uncertainty as to the exact location of the target remained, then it would still be necessary for the subject to scan elements in the vicinity of the target and the possibility of target-noise confusion would still exist.…”
mentioning
confidence: 99%
“…Experimental evidence suggests the middle part of words and strings is the least readily perceptible one (Williams et al 1970;Fudin and Kenny 1972;Eriksen and Eriksen 1974;Wolford and Hollingworth 1974). Contrary to these findings, final letters k in the LVF are even less perceptible than central ones.…”
Section: Letter Positionmentioning
confidence: 76%
“…-an overall decrease of contour perception with increasing eccentricity (Lefton and Haber 1974); -the best performance on outward letters and a worsening towards the fovea (foveally oriented interference, Mackworth 1965); the worst performance on middle letters (Wolford and Hollingworth 1974); -left-right visual field asymmetries for inward letters, with an advantage for the RVF (Bouma 1973).…”
Section: Discussionmentioning
confidence: 99%